Lymphatic Imaging: Current Noninvasive and Invasive Techniques - Schwartz, Fides R.; James, Olga; Kuo, Phillip H.; Witte, Marlys H.; Koweek, Lynne M.; Pabon-Ramos, Waleska M. (Seminars in Interventional Radiology, 2020)
After nearly disappearing, invasive lymphangiography not only has resurged, but new approaches have been developed to guide lymphatic interventions. At the same time, noninvasive lymphatic imaging is playing a larger role in the evaluation of lymphatic pathologies. Lymphangioscintigraphy, computed tomography lymphangiography, and magnetic resonance lymphangiography are increasingly being used as alternatives to invasive diagnostic lymphangiography. The purpose of this article is to review current invasive and noninvasive lymphatic imaging techniques.
Keywords: lymphangioscintigraphy; CT lymphangiography; MR lymphangiography; lymphangiography; interventional radiology